Residues and enantioselective behavior of cyflumetofen from apple production. (15th August 2020) - Quan, Rui; Li, Minmin; Liu, Yongguo; Jin, Nuo; Zhang, Jia; Li, Ruixing; Wang, Fengzhong; Wang, Zhidong; Francis, Frédéric; Kong, Zhiqiang; Fan, Bei
Highlights: The chiral pesticide cyflumetofen is a novel acaricide. Four apple products were analyzed, including slices, juice, wine and vinegar. Fate of cyflumetofen enantiomers in apple processing was systematically studied. Cyflumetofen was selectively degraded during wine and vinegar fermentation. Processing factors were determined in the processing of four apple products. Abstract: The effect of food processing on the level and fate of chiral pesticide residues in apple products has rarely been investigated. In this study, we used ultra-performance convergence chromatography coupled with triple quadrupole mass spectrometry to determine the content of the novel chiral acaricide cyflumetofen. The matrix-matched calibration lines were constructed for apple slices, juice, wine and vinegar, and the determination coefficients (r 2 ) exceeded 0.9954. Acceptable average recoveries were within 81.1% to 119.9%, and the relative standard deviations (RSDs) ranged from 0.8% to 11.0%. Processing effectiveness is represented by the processing factor (PF). The results indicated that the PFs of different procedures (washing, peeling, enzymolysis, fermentation, among others.) were generally less than 1. The reduction of cyflumetofen enantiomers during fermentation was in accordance with first-order kinetics, and stereoselective behavior was observed. This study provides reliable references for the risk assessment of cyflumetofen in the processing of apple products.